Electrohydrodynamic Inkjet – Micro Pattern Fabrication for Printed Electronics Applications - Choi, Kyung-Hyun; Rahman, Khalid; Muhammad, Nauman Malik; Khan, Arshad; Kwon, Ki-Rin; Doh, Yang-Hoi; Kim, Hyung-Chan (IntechOpen, 2011)
None